2005
DOI: 10.1088/0963-0252/14/3/003
|View full text |Cite
|
Sign up to set email alerts
|

Observations of the long-term plasma evolution in a pulsed dc magnetron discharge

Abstract: Using a time-resolved Langmuir probe the temporal evolution of the plasma parameters in a pulsed dc magnetron discharge was determined for a number of positions both inside and outside the magnetic trap. The discharge was operated at a pulse frequency of 2 kHz with a 50% duty cycle, a titanium target and at a fixed argon pressure of 0.53 Pa.The electron density, n e , electron temperature, T e , plasma potential, V p and floating potential, V f have typically two-fold characteristic decay and rise times, which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
14
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 35 publications
4
14
0
Order By: Relevance
“…Sheridan et al 51 reported them for dc discharges in helium and Godyak et al 52 analyzed different non-Maxwellian plasmas with probe diagnostics. In the field of pulsed plasmas, Bäcker and Bradley 37 thoroughly investigated the effects of incorporating magnetrons into the plasma parameters, such as, for instance, the generation of bi-Maxwellian discharges induced by the presence of a magnetic field.…”
Section: ͑7͒mentioning
confidence: 99%
See 2 more Smart Citations
“…Sheridan et al 51 reported them for dc discharges in helium and Godyak et al 52 analyzed different non-Maxwellian plasmas with probe diagnostics. In the field of pulsed plasmas, Bäcker and Bradley 37 thoroughly investigated the effects of incorporating magnetrons into the plasma parameters, such as, for instance, the generation of bi-Maxwellian discharges induced by the presence of a magnetic field.…”
Section: ͑7͒mentioning
confidence: 99%
“…Bäcker and Bradley 37 supposed that secondary electrons from the cathode were firmly pushed into the bulk of the plasma by the contracting sheath, leading to an increase in T e . Using Langmuir probe diagnostics, Glocker showed that ac discharges resulted in electrons that were more energetic than in dc-powered plasmas.…”
Section: Tracking Plasma Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent research involving ionization with high voltage fields 24,25 or magnetrons 26 has shown that pulsed electrical discharges may be superior to a DC discharge. Unlike DC, the pulsed discharges do not permit charge to build up on the surfaces of the electrodes which is a precursor to arcing.…”
Section: American Institute Of Aeronautics and Astronauticsmentioning
confidence: 99%
“…It is caused by small ratio of working time and time of periode t w /T . The repetition frequencies in the order of kHz (with duty cycles about 50 %), so-called mid-frequency discharge, were used in many cases with different types of target materials (Ti targets e. g. in [11]). The measured electron density reached n e ≈ 10 16 m −3 in almost all mentioned works.…”
Section: Introductionmentioning
confidence: 99%